INFLUENCE OF NITROGEN LEVELS AND PLANT DENSITY ON AGRONOMIC WAITS OF MAIZE (ZEA MAYS L.) HYBRIDS IN A FOREST LOCATION - ALOFE , C. O.; OKELEYE, K. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
This study investigated the response of two maize (Zea mays L-) hybrids to four levels of nitrogen (N) (0.100, 200 and 300 kg/ha) at two plant densities (53,300 md 66,600 plants/ ha). The experiment was conducted at tbc Teaching and Research Farm of the Obafemi Awolowo University, Ile-Ife, Nigeria in the early and late cropping seasons of 1985. Design was a randomized complete block (RCBD) with split-split plot arrangement. N was the main plot while varieties and spacing constituted the sub-plots, and sub-sub plots, respectively. Grain yields increased up to 200kg/ ha of applied N while at higher N levels, yield tended to ceil off. Yield of the hybrids varied from 3.0 t/ha at 0kg N/ha to 5.4 t/ha at 300kg N/ ha. N at 200 kg /ha was found adequate for grain yielding during the early season while a lower rate (100 kg N /ha) appeared sufficient for the late season. The effect of effects of N on grain yield were due to an increase in ear length, ear diameter, and number of kennel rows per ear. No significant yield difference was obtained between tbc two (normal and high) densities used indicating that the normal density of 53,300 plants/ ha is adequate for the hybrids used.